1994
DOI: 10.1063/1.358282
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of switching fields in magnetic recording media (invited)

Abstract: Coercivity and other experimental measures of switching field depend upon the time scale of interest. This time-scale dependence has practical importance in magnetic recording, because the effective time scales of writing and storage are very different. A simple model accounts for the time-scale dependence of coercivity in terms of the thermally assisted crossing of an energy barrier whose height is reduced by the applied field. Fitting this barrier-crossing model to data provides an estimate of the volume tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
161
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(170 citation statements)
references
References 28 publications
9
161
0
Order By: Relevance
“…33-can be related to contributions from off-site spin-orbit scattering of the Fe states, which seem also to be responsible for the quenching of the interfacial orbital magnetic moments of Fe as shown in the upper panel of Figure 2. Thus, the type of the particle's surface termination can be deemed of particular importance if the protective shell consists of heavy elements, which possess a large spin-orbit-coupling parameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33-can be related to contributions from off-site spin-orbit scattering of the Fe states, which seem also to be responsible for the quenching of the interfacial orbital magnetic moments of Fe as shown in the upper panel of Figure 2. Thus, the type of the particle's surface termination can be deemed of particular importance if the protective shell consists of heavy elements, which possess a large spin-orbit-coupling parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Examples at three different temperatures can be seen in Figure 5a. For ensembles of non-interacting nanoparticles with diameter d, uniaxial anisotropy K eff and randomly oriented easy axes of magnetization, the temperature dependence of coercivity can be described by Sharrock's equation 33 :…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic H C , H C,dyn , is the field required to bring the magnetization to zero after a characteristic time, t o , and functionally obeys Sharrock's equation. 23 In our calculations, an attempt frequency f o =5ϫ 10 9 Hz is used and we can presume n =1. 22,24,25 From this analysis, the thermal stability factor, defined as ␤ ϵ ⌬E o / k B T, and time independent intrinsic H C , H o , can then be extracted.…”
mentioning
confidence: 99%
“…Sample B being an optimized CoCrPt alloy, its effective anisotropy is of about 9×10 5 J/m3, almost one order of magnitude higher than sample A (see Table 1). The barrier height ΔE, which prevents the magnetization reversal, is thermally activated and depends on the reversal mode [21] [22]. By magnetic after-effect measurements, we have already shown that ΔE for sample B was larger than seen in sample A [13] (see table 1).…”
Section: Introductionmentioning
confidence: 96%